PEMBELAJARAN AKSARA JAWA DILIHAT DARI TEORI BELAJAR PIAGET (STUDI KASUS SEKOLAH DASAR DI KABUPATEN KUDUS) - Dwiana Asih Wiranti; Much Arsyad Fardani; Fisqiyatur Rohmah (Journal Prakarsa Paedagogia, 2024)
This study aims to examine more deeply Jean Piaget's cognitive learning theory and its implications for Javanese language learning in Javanese script material in accordance with the level of thinking of elementary school-age children. This research is a type of quantitative research through a qualitative descriptive approach with a case study approach. Data collection techniques in this study through tests, interviews with teachers, observations, and questionnaires to find out information related to student problems in learning Javanese characters. The problem was found that students had difficulty in reading and writing Javanese characters which stemmed from factors; (1) the difficulty of the Javanese script form which is difficult to distinguish between one letter and several other letters, (2) the non-use of Javanese characters in daily reading and writing activities today, (3) the use of Javanese script learning media that is not appropriate. The sampling technique in this study was carried out using purposive sampling. The results of this study indicate that the cognitive development of children at the concrete operational age stage (7-12 years) in learning Javanese language Javanese script material in elementary schools is adjusted to the age stage, which begins in grade III SD by learning the initial Javanese script (legena script). This is in accordance with the implementation of Jean Piaget's learning theory. It refers to how people grow, adjust, and change over the course of their lives through physical development, personality development, socioemotional development, cognition (thinking) development, and language development.Â Â  In addition to the level of understanding, the models and methods and treatments used also vary. The results of this research can be the basis for teachers to teach so that learning becomes more effective, efficient, and on target. Moreover, to realize the achievement of national education goals